Laser soldering of sapphire substrates using a BaTiAl6O12 thin-film glass sealant. (July 2016) - de Pablos-Martin, A.; Tismer, S.; Benndorf, G.; Mittag, M.; Lorenz, M.; Grundmann, M.; Höche, Th.
Abstract: Two sapphire substrates are tightly bonded through a BaTiAl6 O12 -glass thin film, by irradiation with a nanosecond laser. After the laser process, the composition of the glass sealant changes, due to incorporation of Al2 O3 from the upper substrate. After annealing of the bonded samples (950 °C for 30 minutes) crystalline structures are observed by TEM which are attributed to crystalline BaTiAl6 O12 . These crystals together with Al2 O3 :Ti centers are the responsible of the observed strong blue luminescence of the laser irradiated region upon UV excitation. The structural and optical characterizations of the bonded samples clarify the laser soldering procedure as well as the origin of the luminescence. Bond quality and bond strength were evaluated by scanning acoustic microscopy (SAM) and tensile tests, which results in a tensile stress of nearly 13 MPa, which is an acceptable value for glass sealants. Highlights: Two sapphire substrates were laser-welded through a BaTiAl6 O12 glass thin film. After annealing, the weld shows blue luminescence from UV excitation. Crystalline BaTiAl6 O12 and probably Ti:Al2 O3 originate the observed luminescence.